2009
DOI: 10.1007/s11266-009-9097-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Management of Sports Events Volunteers Through Psychological Contract Theory

Abstract: This paper juxtaposes the expectations of event managers and sports event volunteers in a case study organisation. These are understood within the theoretical framework of the psychological contract. Results show the distinctive contribution volunteers can make to events but also the distinctive challenges they present to event managers. For event managers, volunteers bring: enthusiasm, a good relationship and empathy with the public, and they provide a cheaper labour force. But a major concern is ensuring the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 23 publications
1
61
0
1
Order By: Relevance
“…We broaden this literature by scrutinizing the effects of ideological PC breach and fulfilment on work effort in a sample of volunteers. This article thus adds to an emergent line of research on volunteers' PCs (Farmer & Fedor, 1999;Nichols, 2012;Nichols & Ojala, 2009;Ralston, Downward, & Lumsdon, 2004;Smith, 2004;Starnes, 2007;Taylor, Darcy, Hoye, & Cuskelly, 2006;Vantilborgh et al, 2011a;Vantilborgh et al, 2011b;Vantilborgh et al, 2012). Our study's contributions are threefold.…”
Section: Please Scroll Down For Articlementioning
confidence: 76%
“…We broaden this literature by scrutinizing the effects of ideological PC breach and fulfilment on work effort in a sample of volunteers. This article thus adds to an emergent line of research on volunteers' PCs (Farmer & Fedor, 1999;Nichols, 2012;Nichols & Ojala, 2009;Ralston, Downward, & Lumsdon, 2004;Smith, 2004;Starnes, 2007;Taylor, Darcy, Hoye, & Cuskelly, 2006;Vantilborgh et al, 2011a;Vantilborgh et al, 2011b;Vantilborgh et al, 2012). Our study's contributions are threefold.…”
Section: Please Scroll Down For Articlementioning
confidence: 76%
“…Indeed, personal and public recognition of volunteering has been empirically linked to positive outcomes for the volunteer and nonprofit organization among older adult volunteers in human services organizations (Tang et al, 2009), top internet sites' contributors, but not lower-level contributors (Restivo & van de Rijt, 2014), and a range of non-profits in the art, environment, community, welfare, health, youth, emergency services, religion and other sectors (Stirling, Kilpatrick, & Orpin, 2011). In addition to the recognition of their contributions, research has also found that event volunteers in the UK are motivated by the quality of interpersonal relationships and clear communication of what is expected of them (Nichols & Ojala, 2009). …”
Section: Motivation-enhancing Hr Practicesmentioning
confidence: 99%
“…A few studies have explored the psychological contract of volunteers within the sport setting specifically, however they tended to adopted employee-based frameworks that critics argue do not fully capture the nature and particular nuances of the volunteer work environment and volunteer-organization relationship (Nichols, 2012;Nichols & Ojala, 2009;Vantilborgh et al, 2012). Liao-Troth's (2001) adaption of Rousseau's (2000) PCI to the volunteer context is included in those criticisms as Rousseau's PCI was "designed from a management perspective" (Nichols & Ojala, 2009, p. 376), and is not inclusive of all of the general volunteer elements as uncovered by Smith (2004).…”
Section: Psychological Contract Of Volunteersmentioning
confidence: 99%
“…Kim et al's (2009) investigation of sport event volunteers' contract fulfillment was even further limited to the consideration of only relational elements. In a third sport volunteer study, Nichols and Ojala (2009) used the concept of psychological contract to describe and compare what were perceived to be key contributions of sport event managers and volunteers derived from "a general evaluation of the volunteer programme" (p. 378). The studies conducted to date on sport volunteers have relied on tools developed for the paid workforce from management perspective, have only considered one dimension of the psychological contract, or have only focused on general elements of the psychological contract, thus failing to uncover or consider the range of elements that may be specific to the sport volunteer context, and any particular role there.…”
Section: Psychological Contract Of Volunteersmentioning
confidence: 99%